The impact of COVID-19 lockdown on athletes' subjective vitality: The protective role of resilience and autonomous goal motives - Martínez-González, N.; Atienza, F.; Tomás, I.; Duda, J.; Balaguer, I. (Frontiers in Psychology, 2020)
The lockdown resulting from COVID-19 has had a huge impact on peoples` health. In sport specifically, athletes have had to deal with frustration of their objectives and changes in their usual training routines. The challenging and disruptive situation could hold implications for their well-being. This study examined the effect of the COVID-19 lockdown on changes in athletes` reported eudaimonic well-being (subjective vitality) and goal motives (autonomous and controlled) over time (i.e., pre - and during-lockdown). The relationship of resilience to changes in subjective vitality was also determined, and changes in athletes` goal motives were examined as potential mediators. Participants were 127 Spanish university athletes aged between 18 to 34 years old (M = 21.14; SD = 2.77). Approximately 4 months before the start of the lockdown in Spain (T1), athletes responded to a questionnaire assessing their resilience, goal motives and subjective vitality. Around 6 months later into the lockdown period (T2), athletes` goal motives and subjective vitality were assessed again. Growth Modeling using hierarchical linear models revealed a significant decrease of autonomous goal motives and subjective vitality during the lockdown, but athletes did not show change over time in controlled goal motives.